Karakterisasi berbagai Jenis Bahan Lapisan Kedap, Ketebalan dan Nisbah Bentonit dengan Pasir: Konsep Dasar Pengelolaan Lahan Pasir Pantai - Saparso Saparso; Tohari Tohari; Dja’far Shiddieq; Bambang Setiadi (JOURNAL OF TROPICAL SOILS, 2009)
Characterization of Various Kinds, Thickness and Bentonite Sand Ratio as Hardplain Materials: a Basic Concept for Coastal Sandy Land Management (Saparso, Tohari, D. Shiddieq, and B. Setiadi): Coastal sandy land development  faces  the sand characteristics, the lower holding water capacity and the larger nutrient leaching due to heavier rainfall in the tropics, soil porosity  and without soil layering so it need alternative technology  for  more efficient  harvesting water resources in  supporting  the crop growing. The  laboratory research studied the characteristic of various kind, thickness and ratio of hardplain material was carried out at Laboratory of Agronomy of UNSOED,  Soil Mechanic of GMU.  the SEM and X-RD of  Lemigas Jakarta. Permeability determination by Falling Head which is appropriate measurment  was not significantly different with ELE28-290 permeameter. Permeability of Kokap clay soil and  Nanggulan bentonite were larger than the  rainfall intensity in coastal sandy land.  The Sentolo Vertisol content 68% calcium smectite had permeability 3,7 mm.day-1.  Bentonite permeability were not significantly different due to more than 80% clay mineral composition. Therefore the permeability of natrium bentonite like as  BPIB and  BLUB namely  1.4 x 10-2 and 10-2  mm day-1 were lower than the calcium bentonite like as RMBL and BLBK  permeability namely  4.3 x 10-2  and  2.43 x 10-2 mm day-1. Permeability of 0.5 cm thickness bentonite was not  significantly different than 1.0 dan 1.5 cm thickness and those had very low permeability. Bentonite sand mixture 15 and 20 percent produced bentonite sand agregate  that  had  mesopores by which allowing the drainage and available soil water so that those had water permeability 13.7 dan  10.3 mm day-1 respectively.  The mixture 30-100%  had not significantly different permeability namely 7.3 x 10-2  up to 1.4 10-2 mm day-1. The combination of tickness and the low ratio of  bentonite sand mixutre need to be determined to produce favourable environment in supporting  the plant growth.